2022
DOI: 10.3389/fenvs.2022.981960
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of afrotropical fish communities across river gradients in the Republic of Congo, west central Africa

Abstract: Characterizing functional freshwater biodiversity patterns and understanding community determinants can aid in predicting changes and prioritizing specific conservation management actions. Afrotropical freshwater systems support diverse ecological communities, including many taxonomically undescribed species, yet few studies have been undertaken in this region and they remain poorly understood. Here, we use functional trait-based approaches to describe the functional diversity of fish assemblages in the Republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…This increase in species diversity is likely a result of downstream river widening and the presence of larger pools. These habitats are known to host increased species diversity, specifically larger and more predatory fishes (Bertora et al, 2021;Walsh et al, 2022). At both sites (R1 and R2), we found larger and more piscivorous fishes (Mozambique Tilapia, African Sharptooth Catfish, and Largemouth Bass) occupying larger pools.…”
Section: Discussionmentioning
confidence: 68%
“…This increase in species diversity is likely a result of downstream river widening and the presence of larger pools. These habitats are known to host increased species diversity, specifically larger and more predatory fishes (Bertora et al, 2021;Walsh et al, 2022). At both sites (R1 and R2), we found larger and more piscivorous fishes (Mozambique Tilapia, African Sharptooth Catfish, and Largemouth Bass) occupying larger pools.…”
Section: Discussionmentioning
confidence: 68%
“…Median species richness in the Middle river basin section was lower than in the Upper and Lower river basin sections; however, the Middle section had both more sampling sites and much higher range of species richness. Environmental filtering across river gradients has a strong influence on species richness and diversity ( López‐Delgado et al 2019 , Walsh et al 2022 ). By grouping by section, we are missing local habitat-specific variables which are likely to be driving differences in fish assemblages across a highly heterogenous river network.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to understand the specific microhabitats and fish associations throughout the river basin as this is undoubtedly a driving factor of diversity. For example, river slope and flow conditions exert strong environmental filters on fish community and traits in Neotropical and Afrotropical freshwaters and dispersal between heterogenous habitats may be limited by side channels and swamp habitats ( Caetano et al 2021 , Walsh et al 2022 ). A higher concentration of specialist species is expected to be found in the Upper section as there is more competition for niches ( Sternberg and Kennard 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Species functional traits can be used to better understand fish assemblage structure (Pease et al, 2012; Walsh et al, 2022), quantify the trait‐environment relationships (Brind'Amour et al, 2011; dos Santos et al, 2017; Santos et al, 2019) and assess the response of ecosystem to disturbances, including the introduction of non‐native species into novel environments (Angulo‐Valencia et al, 2022; Dala‐Corte et al, 2016; Lin et al, 2021; Miiller et al, 2021). Consistent with the first hypothesis that functional traits would reflect broad differences in species and their habitat associations within the Great Fish River system, the results of the present study revealed evidence of interspecific variation in functional traits, which appeared to reflect spatial differences in the distribution patterns and species‐environmental relationships.…”
Section: Discussionmentioning
confidence: 99%